CONTEMPORARY SOCIAL CONFLICTS: POSSIBLE CAUSES AND CONSEQUENCES OF VIRTUAL LYNCHINGS - Mercuri Macedo, Karen Tank [UNESP] (Fundacao Univ Tocantins, 2018)
Historically, society does not feel protected by the state and considers institutional justice inefficient and slow. Thereby, people are moved by fear, increasing mistrust and the verge of a war of everybody against everybody. Therefore, persons similar to ban those who think or act in different ways. The insertion of technology in the daily life of contemporary society has made these social practices popularize and gain new dimensions. Although there is a sense of freedom on the Internet, this environment is not exempt from law enforcement for those who disrespect human rights. In this article, we will trace the trajectory of a new social conflict, the Virtual Lynch (MERCURI, 2016): we will seek to identify some principles that indicate its origin; afterwards, we will describe how it occur in the virtual and how this environment strengthens it; and finally, to show the possible consequences for both: the virtual lynchers and the victims.
Keywords: virtual lynching; conflicts; popular; justice; human rights